Can 3T multiparametric magnetic resonance imaging accurately detect prostate cancer extracapsular extension? - Cerantola, Yannick (Canadian Medical Association, 2013)
BACKGROUND: Accurate staging is essential to determine the correct management of patients diagnosed with prostate cancer. We assess the accuracy of 3T multiparametric magnetic resonance imaging (MRI) with endorectal coil (3TemMRI) in detecting prostate cancer local extension. METHODS: We retrospectively reviewed charts from January 2008 to July 2012 from all patients undergoing radical prostatectomy. Patients were only included if 3TemMRI and radical prostatectomy were performed at our institution. Based on the presence of extracapsular extension (ECE) at 3TemMRI, prostate cancer was dichotomized into locally advanced or organ-confined disease. The accuracy of 3TemMRI local staging was then evaluated using definitive pathology as a reference. RESULTS: Overall, 177 radical prostatectomies were performed within the timeframe. After applying exclusion criteria, 60 patients were included in the final analysis. The mean patient age was 67 ± 7 (standard deviation) years. Mean prostate-specific antigen value was 12.7 ± 12.7 ng/L. Based on preoperative characteristics, we considered 38 of the 60 patients (63%) patients high risk. 3TemMRI identified an organ-confined tumour in 46 patients and locally advanced disease in 14 patients. When correlated to final pathology, 3TemMRI specificity, sensitivity, negative and positive predictive values, and accuracy in detecting locally advanced prostate cancer were 90%, 35%, 57%, 79% and 62%, respectively. INTERPRETATION: This study shows that the use of preoperative 3TemMRI can be used to identify organ-confined prostate cancer when locally advanced disease is suspected.